Creatine in adult health and performance: A literature review - Migiel, Marcin; Brynczka, Izabela; Siuta, Natalia; Rypel-Bośka, Joanna; Miaśnikiewicz, Jakub; Goleniewska, Klaudia; Stupecka, Aleksandra; Cecuła, Wiktoria; Ciechomski, Kamil (Quality in Sport, 2025)
Introduction and Purpose: Creatine is a naturally occurring compound widely used as a supplement to enhance high-intensity exercise performance and increase muscle mass. Beyond its muscular benefits, creatine plays a key role in cellular energy homeostasis. There is growing interest in its potential cognitive and therapeutic applications, but several misconceptions about its safety and effects persist. Research Objective: The role of this article is to summarize current evidence on creatine supplementation in adults, focusing on its efficacy for physical performance, its safety profile and emerging roles in cognitive and other health domains. Materials and methods: A literature review of studies published from 2019–2024 in the PubMed database analyzed clinical trials, meta-analyses, and systematic reviews on the effects of PA, using the following keywords: „creatine” ; „performance” ; „aging” ; „cognitive function” ; „depression”. Conclusions: Creatine monohydrate is recognized as the most effective supplement for increasing muscle strength and muscle mass, with consistent benefits observed in both athletes and older adults. Long-term use of recommended doses is well-tolerated. Emerging evidence suggests creatine may also support cognitive function and brain health. Future research should prioritize human studies exploring neurological and mental health applications.